2011
DOI: 10.3390/info2020302
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Approaches to Referential Domains and the On-Line Processing of Referring Expressions in Unscripted Conversation

Abstract: This article describes research investigating the on-line processing of language in unscripted conversational settings. In particular, we focus on the process of formulating and interpreting definite referring expressions. Within this domain we present results of two eye-tracking experiments addressing the problem of how speakers interrogate the referential domain in preparation to speak, how they select an appropriate expression for a given referent, and how addressees interpret these expressions. We aim to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 54 publications
(83 reference statements)
3
37
0
Order By: Relevance
“…Hierarchical incrementality is also unlikely to mediate construction of simpler phrases (e.g., conjuncts), where word order may reflect differences in the order of word activation (axe and saw or saw and axe) or common usage (king and queen but not queen and king). Thus as in studies examining context effects on various aspects of on-line processing (e.g., use of common ground in conversational exchanges; Brown-Schmidt & Konopka, 2011), an emphasis on flexibility requires further specification of how and when different variables shape formulation.…”
Section: Resultsmentioning
confidence: 99%
“…Hierarchical incrementality is also unlikely to mediate construction of simpler phrases (e.g., conjuncts), where word order may reflect differences in the order of word activation (axe and saw or saw and axe) or common usage (king and queen but not queen and king). Thus as in studies examining context effects on various aspects of on-line processing (e.g., use of common ground in conversational exchanges; Brown-Schmidt & Konopka, 2011), an emphasis on flexibility requires further specification of how and when different variables shape formulation.…”
Section: Resultsmentioning
confidence: 99%
“…Test trials included, e.g., a small triangle in common ground and a larger triangle visible to only the speaker. In such situations, speakers were highly successful at designing a referring expression that had the right amount of information for their audience, and only produced size adjectives about 5% of the time; by contrast, in situations where the size-contrast is in common ground, modification rates range from 70 to 90% (Brown-Schmidt and Tanenhaus, 2006;Brown-Schmidt and Konopka, 2011). In other situations, speakers may include in their utterance information that is not already known to the listener (Heller et al, 2012), which falls naturally from observations of Stalnaker (1978) that speakers should contribute new information to common ground.…”
Section: Insights From Language Processingmentioning
confidence: 97%
“…One possible source of this null effect may be the fact that the Infelicitous training trials consisted only of over-informative instructions. It has been reported that naturalistic adjective use contains a large amount of instances in which an adjective is not strictly necessary with respect to the goal of unique reference (Brown-Schmidt & Konopka, 2011). Over-informative adjectives may not impair on-line language processing (Arts, Maes, Noordman, & Jansen, 2011;Davies & Katsos, 2013;Levelt, 1989;Rubio-Fernández, P., 2016;cf., Engelhardt, Demiral, & Ferreira, 2011), and may reflect natural properties of utterance formulation (Belke, 2006;Pechmann, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Scalars in particular are unlikely to be used infelicitously (Brown-Schmidt & Konopka, 2011;Nadig & Sedivy, 2002;Ryskin et al, 2015;Tarenskeen, Broersma, & Geurts, 2015). 5 The instances of infelicitous adjective use experienced in the experimental session was not sufficient to fully counter a lifetime of experience with felicitous scalar adjectives.…”
Section: The Role Of Prior Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation